2021
DOI: 10.3171/2020.7.jns201915
|View full text |Cite
|
Sign up to set email alerts
|

Superselective pseudocontinuous arterial spin labeling in patients with meningioma: utility in prediction of feeding arteries and preoperative embolization feasibility

Abstract: OBJECTIVESuperselective pseudocontinuous arterial spin labeling (ss-pCASL) is an MRI technique in which individual vessels are labeled to trace their perfusion territories. In this study, the authors assessed its merit in defining feeding vessels and gauging preoperative embolization feasibility for patients with meningioma, using digital subtraction angiography (DSA) as the reference method.METHODSThirty-one consecutive patients with meningiomas were prospectively recruited, each undergoing DSA (and embolizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…To this end, preoperative embolization of tumors with abnormal blood supply is encouraged when necessary to reduce intraoperative bleeding and facilitate the surgery. Super-selective embolization of intratumoral vessels [ 12 ] refers to the delivery of a microcatheter into the blood supply artery of a meningioma patient, through which an embolic agent is injected to block the blood flow, prevent intraoperative bleeding, and soften the tumor, thereby reducing the difficulty of surgical resection and facilitating surgical resection [ 13 , 14 ]. However, due to the paucity of related clinical studies, the clinical effectiveness of this procedure has not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, preoperative embolization of tumors with abnormal blood supply is encouraged when necessary to reduce intraoperative bleeding and facilitate the surgery. Super-selective embolization of intratumoral vessels [ 12 ] refers to the delivery of a microcatheter into the blood supply artery of a meningioma patient, through which an embolic agent is injected to block the blood flow, prevent intraoperative bleeding, and soften the tumor, thereby reducing the difficulty of surgical resection and facilitating surgical resection [ 13 , 14 ]. However, due to the paucity of related clinical studies, the clinical effectiveness of this procedure has not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…ASL-based studies have shown promising results for the assessment of pediatric brain tumors, including stratification of malignant and/or high-grade brain tumors, outcome prediction, and vascularity. [57][58][59][60][61][62][63] Kikuchi et al compared the tumor blood flow derived from ASL and the histopathological vascular density in pediatric brain tumors and found that the histopathological vascular density had a significant positive correlation with tumor blood flow, which correlated with the • Combining ADC and CBF measurements can be correctly classified as either low-or high-grade tumors. • ADC and CBF of diffuse midline glioma were similar to those of low-grade tumors.…”
Section: Asl For Pediatric Neuroimagingmentioning
confidence: 99%
“…In particular, for the pre-treatment assessment of tumor vascularity and the feeding arteries, ASL may assist in selecting potential candidates for preoperative DSA and embolization in clinical practice, which may reduce radiation exposure. 63 Acute Encephalopathy with Biphasic Seizure and Late Reduces Diffusion: AESD Acute encephalopathy with biphasic seizure and late reduced diffusion (AESD) is the major etiology of acute infectious encephalopathy in Japanese children (approximately 200 patients per year), and the most common causative pathogen of AESD was human herpesvirus 6. 68 AESD is clinically characterized by biphasic seizures and characteristic diffusion-weighted image (DWI) findings.…”
Section: Asl For Pediatric Neuroimagingmentioning
confidence: 99%
See 2 more Smart Citations